PENGARUH MEDIA PEMBELAJARAN INTERAKTIF YANG DISERTAI PETA KONSEP TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMPN 4 PAYAKUMBUH - dwi astuti, Ricka; Nursyahra, Nursyahra; Megahati, RRP. (STKIP PGRI Sumbar, 2014)
ABSTRACT The results of studying biology class VIII SMP 4 Payakumbuh in the school year 2012/2013 has not been satisfactory, and is under the minimum completeness criteria (KKM). The low student learning outcomes because teachers are still using the media and methods of learning that are less variable in the learning process in the human digestive system material that is abstract. The use of interactive learning media that accompanied the map concept is expected to motivate students to learn actively, creatively, and effectively. This study aimed to examine the effect of the use of interactive learning media that accompanied concept maps on learning outcomes of students SMP 4 Payakumbuh biology. This study is an experimental research study design with randomized control group design only. The population in this study were students of class VIII SMP 4Payakumbuh academic year 2013/2014 which consists of 9 classes. Sampling using purposive sampling, in order to obtain a sample class that is a class 2 VIII6 as the experimental class and the control class as a class VIII9. Form of the test used is an objective test. The technique of data analysis is to examine both the average similarity with the t-test at the 0.05 significance level. The results of the analysis of data obtained while the price of t 2.14 1.67 t table, this means tcount> ttable which means that the hypothesis is accepted. From this study it can be concluded that the results of biological studies students by using interactive learning media that accompanied the concept map material effect on the digestive system biology student learning outcomes using conventional learning in class VIII SMP 4 Payakumbuh.